The impact of pediatric skin disease on self-esteem - K.L. Vivar, MD; L. Kruse, MD (Wolters Kluwer, 2018)
Background: Pediatric skin disorders can affect children's self-esteem, relationships with caregivers and peers, and performance in school and activities. Objective: This review describes common pediatric congenital and acquired dermatologic disorders and the impact that these disorders can have on children's self-esteem. Methods: A review of current, English-language literature was conducted with use of the PubMed database. Search terms included atopic dermatitis, acne, infantile hemangiomas, port wine stains, congenital melanocytic nevi, hidradenitis suppurativa, and self-esteem. Results: During infancy and toddlerhood, skin disorders such as infantile hemangiomas primarily affect the attachment between child and caregiver. School-aged children with port wine stains and atopic dermatitis report increased bullying, teasing, and social isolation. Acne and hidradenitis typically affect older children and teens and these conditions are associated with increased risks of depression and suicidal ideation. Effective management of these conditions has been shown to increase patients' self-esteem. Conclusion: Pediatric dermatologic disorders impact self-esteem throughout childhood. In addition to the surgical and medical management of these disorders, clinicians can also take an active role in the assessment and improvement of the psychosocial impact of these skin disorders. Keywords: self-esteem, port wine stain, infantile hemangioma, congenital melanocytic nevus, acne, hidradenitis suppurativa, atopic dermatitis